Protection of children in armed conflict (Journal of the College of Basic Education, 2022)
Modern wars have deliberately targeted civilians, and attacks on them have often becomeSometimes it is an element of the elements of war and its strategies, as it leads to the forms of violence it takes.The current armed conflicts, as well as the use of advanced weapons in combat, lead to an increase in the number of victims.among civilians, especially children. (1) International humanitarian law has prohibited the abuse of children.He obligated the warring parties to take appropriate measures to make civilians immune from harm.